﻿Potential climatic and elevational range shifts in the Italian narrow endemic Bellevalia webbiana (Asparagaceae) under climate change scenarios - Lorenzo Peruzzi; David Dolci; Alessandro Chiarucci (Nature Conservation, 2022)
The Webb’s hyacinth (Bellevalia webbiana Parl., Asparagaceae) is an Italian narrow endemic species, listed as Endangered (EN A2c) in the IUCN Global Red List of Threatened Species. The range of this bulbous perennial herb is restricted to two disjunct areas of Central Italy, separated by the mountain ridge of Northern Apennine. To evaluate the impact of climate change on this species, we used Ecological Niche Modelling (ENM) to predict future potential distribution under different scenarios, through Maximum entropy algorithm. The estimated potential distribution highlights the vulnerability of Webb’s hyacinth to the effects of climate change. The current potential Area Of Occupancy (AOO) (992 2×2 km cells) is forecast to dramatically decrease in the range 2041–2100, under the scenarios SSP3-7.0 (2070 = –249, 2100 = –682) and SSP5-8.5 (2070 = –372, 2100 = –948). In all future scenarios, the predicted potential distribution shifts towards higher elevations, located in the two main areas in which the species currently occurs. This could imply a loss of the current genetic differentiation documented at the population level. To overcome these problems, in addition to assisted colonization, an ex situ conservation programme should be planned.